Intelligent watermarking techniques - Pan, Jeng-Shyang; Huang, Hsiang-Cheh; Jain, L. C. (Series on innovative intelligence, 2004)
Watermarking techniques involve the concealment of information withina text or images and the transmission of this information to thereceiver with minimum distortion. This is a very new area ofresearch. The techniques will have a significant effect on defence, business, copyright protection and other fields where informationneeds to be protected at all costs from attackers. This book presents the recent advances in the theory andimplementation of watermarking techniques. It brings together, for thefirst time, the successful applications of intelligent paradigms(including comparisons with convent.